The estimation of GHG emissions for hotels in Asian Institute of Technology and Chiang Mai Hill 2000, Thailand - Supansa, Luansak (International Journal of Agricultural Sciences, 2015)
In the tourism sector, hotel industry is one of the most important sub-sector. This hotel industry emits greenhouse gas (GHG) emissions mainly carbon dioxide (CO2) by consuming large amount of energy, water, and non-renewable resources in service operation everyday on basis. This paper presents results of analysis how much does the GHG emissions release in hotel. The Asian Institute of Technology Conference Center and Chiang Mai Hill 2000, Chiang Mai, Thailand have successfully estimated GHG emissions by using Bilan CarboneÂ® tool. The mitigation options are to encourage low carbon dioxide hotels. The data collection was done by questionnaires, interviews, and observations in both of them hotels. The results of annual GHG emissions contributor both Chiang Mai Hill 2000 as 3,844 t CO2 and at AITCC about 1,011 t CO2. Energy use is a major emission contributor followed by travel, property, input material, waste generated, and freight. Higher number of guests/tourists flow, effected higher used of facilities such as electricity, air conditioning, lighting, and food & beverage. Larger size hotel service quality, greater guest room service, wide range of building area, greater facilities, and large functional are consumed higher energy and materials. As well as, the higher rate of room turning can also increase of emissions. Moreover, Chiang Mai Hill 2000 tends to take transportation which have longer distance than AITCC. Therefore, increasing higher journal distance generated higher GHG emissions as well. The short term and long term mitigation plans can also be taken into consideration to reduce GHG emissions. The recommendation of short term mitigation plans can be applied directly in both hotels thus, increasing awareness about climate change and energy conservation among uses. The long term mitigation plans recommends to give â€œGreen Hotelâ€ award to successful hotels for reducing GHG emissions in hotel. These plans can be incorporated the Thailandâ€™s government policy to reduce the impacts of climate change to the hotel industry.Â